2011
DOI: 10.1111/j.1742-481x.2011.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of presentation of pressure ulcers in traumatic spinal cord injured patients in University College Hospital, Ibadan

Abstract: The neurosurgery division in University College Hospital (U.C.H.) admits approximately one traumatic spinal cord injured (SCI) patient per week, most of whom stay a minimum of 42 days on admission. A common complication in these patients is the development of pressure ulcers, which contributes to a longer hospital stay and increased hospital expenses. The purpose of this study was to investigate the pattern of presentation of pressure ulcers in patients on admission and to propose policies or protocols to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…13,54 In purely economic terms, PUs are very expensive. 17,56,60 Cost estimates for PU care in all-comers have been reported as high as $9000 Canadian a month for community dwellers with high grade ulcers, $130 000 American per hospital admission for hospital-acquired ulcers in the United States and up to 4% of the National Health Service Expenditure in the UK annually. [60][61][62] Although such estimates are difficult to extrapolate to developing world settings, it has been reported that PUs account for one-fourth of the cost of caring for SCI patients in Nigeria.…”
Section: Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…13,54 In purely economic terms, PUs are very expensive. 17,56,60 Cost estimates for PU care in all-comers have been reported as high as $9000 Canadian a month for community dwellers with high grade ulcers, $130 000 American per hospital admission for hospital-acquired ulcers in the United States and up to 4% of the National Health Service Expenditure in the UK annually. [60][61][62] Although such estimates are difficult to extrapolate to developing world settings, it has been reported that PUs account for one-fourth of the cost of caring for SCI patients in Nigeria.…”
Section: Risk Factorsmentioning
confidence: 99%
“…[60][61][62] Although such estimates are difficult to extrapolate to developing world settings, it has been reported that PUs account for one-fourth of the cost of caring for SCI patients in Nigeria. 17 Although imperfect, these cost estimates certainly highlight the financial toll of PUs.…”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…As noted in other publications, there was a male preponderance. 1,4,6,10,11 The number of males with SCI in the period was more than three times that of the females. The male, being more risk taking, is prone to injury in general compared with the females.…”
Section: Discussionmentioning
confidence: 95%